UJI KONSENTRASI CAIRAN PERASAN DAUN KENIKIR(Tagetes patula Juss) TERHADAP MORTALITAS ULAT PENGGULUNG DAUN (Lamprosema indica ) PADA TANAMAN UBI JALAR - Rahayu, M; Pakki, Terry; Saputri, Ramlia (Jurnal Agroteknos, 2012)
This experiment was conducted at the Plant Pest and Disease Laboratory, taking place in October 2011 to Januari 2012. This research compiled based on completely randomized design (RAL) with 5 (five) treatments and 3 treatment.   The treatment were control (P0), dilution of juice of leaf kenikir 10 mL/ water litre (P1), dilution of juice of leaf kenikir 15 mL/ litre (P2) dilution of juice of leaf kenikir 20 mL/ litre (P3), dilution of juice of leaf kenikir 25 mL/litre (P4), therefore were 15 treatment units. Parameter observed was insect mortality, observed at 12, 24, 36, and 48 hours after application (JSA). Research results indicated that highest average of leaf winder caterpillar mortality (Lamprosema indica) was at treatment P4 (dilution of juice of leaf kenikir 25 mL/ litre), equal to 63,33 % at observation of 36 JSA. Keyword: kenikir’s leaf, mortality, Lamprosema indica, sweet potato